Incubation of Oryzias woworae Eggs at Different Temperature on Embryo Development and Hatching Performance - Nisa Nafiyanti; Mustahal Mustahal; Mas Bayu Syamsunarno; Muh. Herjayanto (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Oryzias woworae is one of Muna Island's endemic fish, Sulawesi, which needs to be developed in cultivation and can be used as ornamental fish with high economic value. However, information on fish farming is not yet well available, especially at egg incubation temperatures. This study aims to determine the optimal temperature of the incubation water medium for the hatching performance of O. woworae eggs. The study used experimental methods with the treatment of differences in egg incubation temperatures at 24-26ÃÂ°C (temperature fluctuations in the laboratory), 24ÃÂ°C, 28ÃÂ°C and 32ÃÂ°C. The research parameters were analyzed descriptively, namely embryogenesis, hatching time, and hatching rates. The results showed that differences in incubation temperature affected the embryogenesis of O. woworae eggs. The obtained fastest time for hatching eggs O. woworae at a temperature of 32ÃÂ°C with six days 5 hours 49 minutes and 100% hatching. The egg incubation temperature 24-26ÃÂ°C is the lowest hatching time and hatching rate, nine days 11 hours 38 minutes and 53.33%. The use of 32ÃÂ°C in the incubation medium is the optimal temperature to accelerate embryogenesis and the hatching rate of O. woworae eggs.